2011
DOI: 10.1002/ijc.26345
|View full text |Cite
|
Sign up to set email alerts
|

Different DNA damage and cell cycle checkpoint control in low‐ and high‐risk human papillomavirus infections of the vulva

Abstract: Human papillomavirus (HPV) infections may result in benign hyperplasia, caused by low-risk HPV types, or (pre)malignant lesions caused by high-risk HPV types. The molecular basis of this difference in malignant potential is not completely understood. Here, we performed gene profiling of different HPV infected vulvar tissues (condylomata acuminata (n 5 5), usual type vulvar intraepithelial neoplasia (uVIN) (n 5 9)) and control samples (n 5 14) using Affymetrix Human U133A plus 2 GeneChips. Data were analyzed us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
96
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(97 citation statements)
references
References 45 publications
0
96
0
1
Order By: Relevance
“…We propose that the increased activity of the DNA repair system in late stages of HPV infection and during HPV-driven carcinogenesis reported in previous studies6 is a secondary effect of substantial DNA damage present in the host cells and not induced by HPV. Contrarily, we suggest that HPV impairs the DNA damage detection and repair system early in infection, which allows the accumulation of mutations that can be beneficial for the initiation of a persistent viral infection and carcinogenesis process.…”
Section: Discussionmentioning
confidence: 58%
“…We propose that the increased activity of the DNA repair system in late stages of HPV infection and during HPV-driven carcinogenesis reported in previous studies6 is a secondary effect of substantial DNA damage present in the host cells and not induced by HPV. Contrarily, we suggest that HPV impairs the DNA damage detection and repair system early in infection, which allows the accumulation of mutations that can be beneficial for the initiation of a persistent viral infection and carcinogenesis process.…”
Section: Discussionmentioning
confidence: 58%
“…E7 is able to accelerate the degradation of claspin, a protein necessary for Chk1 activation [61]. Consistent with this, in a recent study comparing gene profiles between low- and high-risk HPV-infected vulvar tissues, the tissues that are infected with high-risk HPV appear to have more DNA damage and increased expression of DDR markers [62]. These data also suggest that the genome instability caused by HPV infection has multiple causes, and many DDR pathways may contribute to it.…”
Section: Viral Modulation Of Cell Cycle Tumor Suppressor Proteins and mentioning
confidence: 75%
“…These effects of E7 are due to inactivation of the Rb family of tumor suppressors that limit DNA damage (19). Microarray analysis of vulvar tissue infected with both low-risk and/or high-risk HPV types indicated that FANCA, FANCD2, and other DNA damage markers were significantly induced following high-risk HPV infection, along with increased DNA damage in the tissues (30). And finally, using a computational biology approach, a link between HPV16 and the FA DNA repair pathway was identified and then validated experimentally by evaluating the impact of overexpressing E6 or E7 proteins in primary fibroblasts and keratinocytes using global gene expression analysis (31).…”
Section: Discussionmentioning
confidence: 99%